Head Pulsation Signal Analysis for 3-Axis Head-Worn Accelerometers - Olli Lahdenoja; Tero Hurnanen; Juho Koskinen; Matti Kaisti; Kim Munck; Samuel Emil Schmidt; Tero Koivisto; Mikko Pänkäälä (United States, 2025)
Previously, using single-axis accelerometers, it has been proposed that in conditions such as traumatic brain injury (TBI) the brain pulsation signal characteristics change, potentially due to changes induced by the impact to the brain. In this paper, we aim to validate the use of a custom built embedded measurement system towards the analysis of the head pulsation signals. The system comprises of several synchronized high sampling rate 3-axis accelerometers and a simultaneous chest ECG. In our case three accelerometers on the surface of human head are used (in left temple, forehead and right temple), while the subject were in supine position. To illustrate that a proper signal quality may be extracted, we derive heart rate (HR) and heart rate variability (HRV) from each sensor and each axis for each of five healthy male volunteers. The results are reported against ECG as the ground truth. This study will build ground for further clinical trial utilizing multi-axial accelerometers to study both healthy and diseased subjects (e.g. TBI patients).
CinC Proceedings